Chinese and South Asian ethnicity, immigration status and head and neck cancer outcomes: A population based study. (February 2021) - Noel, Christopher W.; Sutradhar, Rinku; Li, Qing; Forner, David; Hallet, Julie; Cheung, Matthew; Singh, Simron; Coburn, Natalie G.; Eskander, Antoine
Highlights: This work disentangles the relative effects of ethnicity and immigration on head and neck cancer (HNC) outcomes. In Ontario Canada, HNC patients experience a 'healthy immigrant effect'. HNC patients of Chinese ethnicity experience improved survival relative to the general population. Abstract: Objective: While it is known that certain ethnic and immigrant groups are at increased risk of developing head and neck cancer, the individual effects of immigration status and ethnicity on head and neck cancer outcomes is less clear. We sought examine the independent effects of immigration and Chinese and South Asian ethnicity on overall survival in a head and neck cancer patient population. Methods: This was a population-based retrospective matched cohort study using linked Ontario administrative databases between 1994 and 2017. Incident cancer cases were captured in long-standing residents of Chinese and South Asian ethnicity, Chinese and South Asian immigrants, as well as a reference population. Subjects were followed until death. A hard-matching approach was used to adjust for key differences and ensure both groups were balanced with respect to age, sex and cancer site. Cox proportional hazard models were used to estimate the impact of Chinese and South Asian ethnicity on overall survival while further adjusting for baseline covariates. Results: Among 1639 immigrants with head and neck cancer, matched to 3278 controls, the overall 5-year survival rate was 66% and 59%, respectively. After adjusting for between group-differences, all-cause mortality was lower for immigrants (HR 0.76[95%CI 0.69–0.83]) and individuals of Chinese ethnicity (HR 0.78[95%CI 0.68–0.90]), relative to the general population. Conclusions: In Ontario, immigrants experience lower mortality rates following a head and neck cancer diagnosis. Individuals of Chinese ethnicity with head and neck cancer experience a survival advantage, relative to South Asian individuals and the general population.